2016
DOI: 10.3390/ijerph13121212
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Genotoxicity of Long-Term Occupational Exposure to Low Levels of BTEX in Gas Station Workers

Abstract: Atmospheric benzene, toluene, ethylbenzene, and xylenes (BTEX) can lead to multiple health injuries. However, what remains uncertain is the effect of long-term exposure to low levels of BTEX. Thus, we determined the BTEX levels in the air from the refueling and office areas in gas stations. Then we collected workers’ (200 refueling vs. 52 office workers) peripheral blood samples to analyze the serum total-superoxide dismutase (T-SOD), glutathione (GSH), malondialdehyde (MDA), and 8-hydroxydeoxyguanosine (8-OHd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 27 publications
5
35
0
1
Order By: Relevance
“…Their sources, including in this work’s study region, include vehicular exhaust, gas stations, industrial activity, landfill sites, municipal solid waste (MSW) stations, and combustion for domestic heating (Bruno et al, 2008; Carrieri et al, 2006; Chiriac et al, 2007, 2011; Correa et al, 2012; Durmusoglu et al, 2010; Jiang et al, 2017; Kim et al, 2008; Kountouriotis et al, 2014; Marć et al, 2016; Sairat et al, 2015; Terrés et al, 2010; Wu et al, 2006; Xiong et al, 2016). Past work has shown that more than 45% of total VOC emissions, such as for benzene and toluene, in Mexico City, the United Kingdom, and Los Angeles stemmed from gas stations, evaporation of petrol, and motor vehicle emissions (Correa et al, 2012; Durmusoglu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Their sources, including in this work’s study region, include vehicular exhaust, gas stations, industrial activity, landfill sites, municipal solid waste (MSW) stations, and combustion for domestic heating (Bruno et al, 2008; Carrieri et al, 2006; Chiriac et al, 2007, 2011; Correa et al, 2012; Durmusoglu et al, 2010; Jiang et al, 2017; Kim et al, 2008; Kountouriotis et al, 2014; Marć et al, 2016; Sairat et al, 2015; Terrés et al, 2010; Wu et al, 2006; Xiong et al, 2016). Past work has shown that more than 45% of total VOC emissions, such as for benzene and toluene, in Mexico City, the United Kingdom, and Los Angeles stemmed from gas stations, evaporation of petrol, and motor vehicle emissions (Correa et al, 2012; Durmusoglu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, our results suggest that oxidative damage to DNA occurred in these subjects owing to benzene exposure. Other authors found significantly higher 8-OHdG concentrations in gasoline station attendants [12] , [29] , [30] and policemen [31] exposed to low environmental concentrations of benzene, in children co-exposed to benzene toluene and polycyclic aromatic hydrocarbons [32] and in teenagers [27] . However, not all studies report a strong association between 8-OHdG concentrations and environmental exposure to benzene [33] .…”
Section: Discussionmentioning
confidence: 90%
“…Gasoline contains more than 150 chemicals including benzene, toluene, xylene, and phenolic compounds such as VOCs and PAHs (Shaikh et al ., 2018). Studies in different countries reported that fuel filling station attendants are continuously exposed to petroleum components through skin contact, inhalation and chronic exposure may cause respiratory, blood disorders, and genotoxicity (Cezar‐Vaz et al ., 2012; Abou‐El Wafa et al ., 2015; Rahul et al ., 2016; Xiong et al ., 2016). The present study focused on monitoring workplace pollutants and genotoxicity effects among fuel filling station workers.…”
Section: Discussionmentioning
confidence: 99%
“…The 8‐OHdG forms a alkali pair with pyrimidine base (cytosine) and purine base (adenine) and increases the rate of spontaneous mutations incorporated into DNA (Fenga et al ., 2017;Pawlas et al ., 2017). A study carried among the gas station workers (Xiong et al ., 2016) suggested that the endpoints of oxidative stress and genotoxicity are both useful biomarkers (of exposure and effect, respectively) of occupational exposure to low levels of BTEX (Benzene, Tolune, Ethylbenzene, and Xylene).…”
Section: Introductionmentioning
confidence: 99%